Institutional Improvement of Public Interest Litigation for Personal Information Protection from the Perspective of the Procuratorial Public Interest Litigation Law - Wenhua Wang (Academic Journal of Law and Society, 2026)
Public interest litigation for personal information protection represents a significant expansion of the public interest litigation system in the digital age. Its institutional improvement bears profound significance for safeguarding social public interests and promoting the sound development of the digital economy. This article has conducted its analysis from three dimensions: the justification of public interest, the orientation of litigation types, and the order of priority among initiating subjects. It maintains that in the big data environment, personal information has transcended the attribute of purely private rights and carries a notable connotation of public interest. Adopting the abstract standard of "unspecified persons" to identify "numerous" is more consistent with the original intent of the public interest litigation system. With respect to litigation types, Article 70 of the Personal Information Protection Law should be interpreted as encompassing both civil and administrative public interest litigation. The two types function respectively at the levels of regulating infringements and urging regulatory oversight, and a progressive coordination mechanism of "administrative public interest litigation first, civil public interest litigation following" should be established. With respect to the order of priority among initiating subjects, based on the professional capacity and functional positioning of the procuratorial organs, they should be placed in the first-priority position, so as to effectively drive the operation of the system. In the future, with the formal promulgation of the Procuratorial Public Interest Litigation Law, the relevant rules are expected to be further clarified, and the practical application of public interest litigation for personal information protection will continue to improve, thereby better achieving the maximum protection of the public interest in digital governance.